POTENSI BENGKUANG ( PACHYRIZUS EROSUS ) SEBAGAI ESTROGEN ALAMI PADA MENCIT PREMENOPOUSE - Novi Primiani, Cicilia; Rofiah H, Nasrul; Kiswardianta, R. Bekti (IKIP PGRI MADIUN, 2013)
Orientation: This study examined the possibility of using yam bean as a natural estrogen for mice in their premenopausal stage.Research Purpose: This research aimed for doing examination to the phytoestrogen contains of Yam Bean, its dynamic in the serum and also its potential to the female white mice.Motivation for the study: This research provides the benefit of consuming yam bean to increase the estrogen in mice body. Estrogen hormone mostly used by people especially woman to prevent and medicinal of the disease. Yam Bean is a group of phytoestrogen plant because it contains isoflavonoid with chemical structure that similar with estrogen hormone.Reasearch design, Approach, and Method: This research using pattern experiment approach of Complete Random Design with treatment giving of Yam Bean and daidzein synthesis compound for 24 white mice from the kind of Sprague Dawley in the age of 5 months for 24 days. Daidzein dosage that given based daidzein level in the 1.5 ml of Yam Bean distillate. Blood taking conducted in the 3 fractions (8th, 16th, and 24th hour after treatment). Dissection and uterus organ taking conducted in the 25th day, blood smear making of tissue with HE coloring. Daidzein level test is analyzed with HPLC method. Structure alteration of uterus tissue analyzed descriptively to the endometrial, miometrial and uterus mucosa layer.Main Findings: Research result shows that daidzein level in serum with Yam Bean distillate giving in the fraction 1, 2, and 3 are lower than daidzein synthesis compound giving. Endometrial tissue of uterus having proliferation, and also uterine gland proliferation in the treatment giving of Yam Bean distillate. The conclusion shows that Yam Bean can improve daidzein level that has potential as natural estrogen.Contribution/Value-add: The process leads other researcher to do the next experiment related to yam bean as a natural estrogen and its possibility of using yam bean as a natural estrogen for human.